Desenvolvimento de uma plataforma para integração e disponibilização de dados do setor agropecuário - Lopes, Rafael Silveira (2022)
Information and Communication Technology leads the agricultural scenario to improve the techniques used and development in the sector. In this environment, the volume of data generated in a short time is large. In addition, much information regarding agricultural indicators is dispersed in several databases and is sometimes difficult for users to access. New techniques to manage this data have become as important as the workforce, thus allowing, among other advantages, cost reduction and production planning. In this context, there was a demand for the centralization of agricultural data by two types of stakeholders of the Observatório da Embrapa Pecuária Sul. Therefore, this work proposes, implements and evaluates the integration and availability of data from indicators of the agricultural production chain to different types of stakeholders through a web platform. The application aims to serve as an instrument for understanding the current scenario and the planning future scenarios of agriculture in the southern region of Brazil, as well as to assist in decision-making and to encourage public policies in the sector. The methodology used in the work was divided into three segments: tool design; modeling and prototyping; and implementation and validation. As a result, in the data collection process, approximately 126 agricultural indicators were identified, organized and verified. In addition, the construction of the platform allows the storage, structuring and availability of historical series of different agricultural segments through spreadsheets and graphs. Through the validation of the system with the stakeholders using an adaptation of the Technology Acceptance Model (TAM), a high degree of ac ceptance of the system was obtained, either as a way of improving decision-making and performance in research work in the agricultural sector, or for the ease of understanding of the functionality provided.